Severe hypoalbuminemia in patient with pulmonary edema and pleural effusion: a case report - Wulandary, Martika Esty; Sofandi, Aditya Azwar (International Journal of Research in Medical Sciences, 2024)
Hypoalbuminemia is a recognized risk factor for mortality and poor outcomes in various clinical contexts. This case report aims to discuss the case and management of severe hypoalbuminemia in a 30-year-old female patient with pulmonary edema and pleural effusion at RSUD Bima. A 30-year-old female with a history of tuberculosis was admitted with worsening shortness of breath, nosebleed, abdominal and breast enlargement, hair loss over the past 2 months, tired, joint pain, swelling in both legs, ulcers on the oral mucosa, and butterfly rash. She exhibited signs of anaemia, hypoalbuminemia, and ascites. X-ray thorax showed cardiomegaly, pulmonary edema, and bilateral pleural effusion. Diagnoses included dyspnea due to pulmonary edema, severe hypoalbuminemia, anaemia, thrombocytopenia, and suspected SLE. Treatment involved oxygen, IV octalbin 25% 100cc, medications, and an extra protein diet. After three days, her albumin levels improved. Hypoalbuminemia can cause pleural effusion by reducing oncotic pressure, leading to fluid buildup. In SLE, it may result from inflammation, malnutrition, or protein loss. Management includes addressing causes, nutritional support, and careful albumin administration.